Os pilares conceituais que unificam a educação das Escuelitas Autónomas do Exército Zapatista de Libertação Nacional – EZLN. - Schimidt, Nilvana Scalco (2022)
The present research aims the investigation of the Zapatista education, particularly the Escuelitas Autônomas of Zapatista Army of National Liberation (EZLN), in the State of Chiapas, Mexico. The general objective focuses on the pillars that unify the concept of non-formal education of the Escuelitas Autónomas of the EZLN. According to studies carried out to date on the topic, the Zapatista Movement became known in the world, for the way of existence based both on self-management and on anticolonialism and anticapitalism. This philosophical current is contrary to any form of domination and power of the state. In this sense, as education is one of the Movement's priorities, it is expressed in the existence of its Escuelitas Autónomas. This is a radical conception of autonomous and democratic educational formation. During the emerging process, the development and consolidation of this Movement were possible to apprehend in the proposal of non-formal education, unity in diversity put into practice, through the philosophy that guides the entire Movement mentioned above. For this reason, we ask: What are the conceptual pillars that enable unity in the diversity of non-formal education in the Escuelitas Autônomas? To answer this question, we will use as a theoretical contribution, the main line of this Movement, consulted in the primary sources, identified in the ELZN documents, among them, letters, announcements, interviews, reports, and essays by subcommander Marcos, in addition to 8secondary and theoretical sources, such as the works of Galeano (2019), Fernandes (1977, 1981), Ianni (1976), Morel (2017, 2018), among others that were used during the research, which is characterized by a qualitative approach